Portfolio-based Writing Instruction as a Venue to Provide Corrective Feedback on EFL Learners’ Writing Performance - Hussein Meihami; Fateme Husseini; Rahman Sahragard (Journal of Modern Research in English Language Studies)
It is an underestimated topic whether or not providing corrective feedback through portfolio-based writing instruction can be effective. Hence, the purpose of the current study was to investigate the effect of providing corrective feedback through portfolio-based writing instruction on the overall and componential writing performance of the Iranian intermediate EFL learners. To that end, 44 intermediate EFL learners participated in a writing program aiming to develop the writing skill of the L2 learners. The participants were divided into the experimental group (N = 20) in which they received the corrective feedback on their writing through the portfolio-based writing, and the control group (N = 24) who received the traditional paper-and-pen corrective feedback on their writing. A pre-test/post-test design was administrated to address the purpose of the study. The results indicated that the experimental group significantly outperformed the control group both in overall and componential writing performance. Thus, it can be concluded that providing corrective feedback through portfolio-based writing can be constructive in developing intermediate EFL learners writing performance. This may be due to the features which portfolio-based writing brings to the L2 writing classroom including developing the motivation of the L2 learners to write, pushing them to be more autonomous in their learning, helping them to reflect upon their writing, and making the learners conscious about the process of writing. Thus, portfolio-based instruction can be thought of a collaborative way to provide corrective feedback on L2 learners writing performance. The study carries some implications for L2 writing teachers and learners.